Investigating Communicative Language Teaching Barriers for English Students in Higher Education - Maram Miftah Aldizeeri; Siti Nur’Aini; Dias Andris Susanto (VELES Voices of English Language Education Society, 2023)
Teaching English as a foreign language presents unique challenges. This research delves into the hurdles faced by English Language Department students at Al-Mergib University, particularly in active participation during the learning process. The study also explores the pedagogical strategies employed by Al-Mergib University instructors, with a focus on communicative language teaching (CLT). Through an applied research approach, the root causes of these challenges and potential solutions are investigated. Data were gathered from five teachers and ten students to offer deeper insights. Findings indicate a mixed teaching approach in Libyan classrooms, while many educators utilize interactive methods such as collaborative learning, others remain reliant on traditional techniques. The results highlight the necessity for teachers to adapt their strategies in response to evolving student needs. A significant challenge for students was understanding lectures, often due to rapid speech and limited vocabulary exposure, hampering language and vocabulary development. The study underscores the importance of targeted teaching practices, fostering student collaboration, and creating a dynamic learning environment. Enhancing students' confidence in English is further facilitated by encouraging its use outside the classroom setting. This research holds valuable implications for language education, curriculum development, teacher training, and the advancement of efficacious English communication skills.